THE DETERMINANT ROLE OF PATIENT EXPERIENCE IN THE RELATIONSHIP BETWEEN HOSPITAL MARKETING AND PATIENT SATISFACTION - Lailatul Kodriyah; Jok Thikuly Gang (Universitas Kusuma Husada Surakarta, 2026)
Background: Rising competition among hospitals has heightened the importance of effective marketing strategies to improve patient satisfaction. Nonetheless, the success of these strategies relies not only on marketing efforts but also on patients’ experiences during healthcare delivery. This study investigates the crucial role of patient experience in linking hospital marketing to patient satisfaction within both public and private hospitals in Malang Regency, Indonesia. Methods: A cross-sectional study was carried out with 403 patients, consisting of 100 from a public hospital and 303 from two private hospitals, chosen via proportionate stratified random sampling. Data collection employed a validated and reliable structured questionnaire. Hierarchical Multiple Regression analyzed how patient experience adds to the link between hospital marketing and patient satisfaction.Results: The findings revealed that hospital marketing significantly influenced patient satisfaction, accounting for 34.1% of the variance. After patient experience was incorporated into the regression model, the explanatory power increased to 64.1%, representing an additional 30.0% of explained variance. In the final model, patient experience demonstrated a stronger effect on patient satisfaction than hospital marketing, indicating its substantial contribution to improving the model’s predictive ability. Conclusion: The patient experience plays a vital role in strengthening the link between hospital marketing and patient satisfaction. Hospitals need to coordinate their marketing strategies with efforts to enhance patient experiences, including providing responsive service, reducing wait times, improving communication between patients and staff, and fostering a safe, comfortable, and patient-focused setting.